Verification of the Heska Element Point‐of‐Care blood gas instrument for use with venous blood from alpacas and llamas, with determination of reference intervals. (12th July 2018) - Viesselmann, Lisa C.; Videla, Ricardo; Flatland, Bente
Abstract : Background: The Heska Element POC ("EPOC") is a blood gas instrument intended for use with canine, feline, and equine whole blood; no verification for use with camelid specimens has been reported. Objectives: Using camelid specimens and commercial quality control materials (QCM), we investigatee EPOC analytical performance and establish EPOC camelid reference intervals (RIs). Methods: Camelid blood (n = 124) was analyzed using the EPOC (pH, p CO2, p O2, HCO3, base excess, SO2, sodium, potassium, chloride, ionized calcium, TCO2, anion gap, HCT, HGB, glucose, lactate, and creatinine); plasma was analyzed using a Roche Cobas c501 (sodium, potassium, chloride, TCO2, anion gap, glucose, and creatinine). Method comparison data were assessed using Pearson's correlation, Passing‐Bablok regression, and Bland‐Altman plots. EPOC precision was evaluated using QCM and camelid blood. Results: For all measurands except anion gap, the EPOC vs Cobas instrument correlation was r > .85. Except for p O2 and p CO2, EPOC precision (QCM and blood) ranged from a repeatability CV <1%‐6.3%. Mild constant bias for chloride, glucose, TCO2, anion gap, and creatinine, and mild proportional bias for chloride, glucose, and anion gap were present. The total error (QCM data) for the EPOC instrument was below the ASVCP‐recommended allowable total error. Alpacas had higher potassium and lactate, while llamas had higher creatinine, sodium, chloride, ionized calcium, p O2, and SO2 . Statistical RIs based on alpaca (n = 74‐96) and llama data (n = 12‐17) are reported descriptively. Conclusions: The EPOC analyzer shows good performance with camelid blood. A lack of complete agreement with automated chemistry analyzers highlights the importance of interpreting patient data using instrument‐specific RIs.